2015
DOI: 10.1007/s00198-015-3390-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hip fracture in very old people: a population-based study

Abstract: SummaryKnowledge of risk factors for hip fracture among very old people is limited. Walking indoors with help from ≤1 person, Parkinson’s disease, currently smoking, delirium in the previous month, underweight, and age were associated with increased risk of hip fracture and could be important for preventive strategy development.IntroductionThe purpose of this study is to investigate risk factors for hip fracture among a representative sample of very old people.MethodsIn total, 953 participants from the Umeå 85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 52 publications
1
39
0
16
Order By: Relevance
“…Population-based studies in this country are limited secondary to lack of a high-quality national database, but other countries with similar socioeconomic structures suggest a bleak picture for older adults who sustain falls and concomitant fractures with dementia (Wiklund et al, 2015). Recently, it has been suggested that up to 90% of hospitalizations in patients with dementia are related to falls (Harvey, Mitchell, Brodaty, Draper, & Close, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population-based studies in this country are limited secondary to lack of a high-quality national database, but other countries with similar socioeconomic structures suggest a bleak picture for older adults who sustain falls and concomitant fractures with dementia (Wiklund et al, 2015). Recently, it has been suggested that up to 90% of hospitalizations in patients with dementia are related to falls (Harvey, Mitchell, Brodaty, Draper, & Close, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Early outcomes are promising (Kelly & Kates, 2015), but long-term effects with meaningful functional outcomes are decidedly lacking, mostly secondary to study design. Many of these studies focus on cohorts of database-driven mortality results (Wiklund et al, 2015). Other studies are based on standard-of-care paradigm shifts in consecutive patient cohorts (Della Rocca et al, 2013), focusing on in-hospital mortality, complications, and re-admissions.…”
Section: Discussionmentioning
confidence: 99%
“…Neck of femur and proximal femoral fractures predominantly occur in people over the age of 65, with a higher occurrence in older women . The presence of dementia is a significant issue in patients with hip fractures with 30–45% of this population having a diagnosis of dementia . Despite this, many randomised controlled trials investigating hip fractures have excluded patients with dementia and cognitive impairment …”
Section: Introductionmentioning
confidence: 99%
“…Several reports from different study populations have shown people with dementia and cognitive impairment have a higher prevalence and risk of hip fracture (see Supplementary references) . However, these studies did not consider bone mineral density (BMD).…”
Section: Introductionmentioning
confidence: 99%
“…3 Several reports from different study populations have shown people with dementia and cognitive impairment have a higher prevalence and risk of hip fracture (see Supplementary references). [4][5][6] However, these studies did not consider bone mineral density (BMD). Most studies only examined the relationship between dementia and fractures at the hip, but not at other sites.…”
Section: Introductionmentioning
confidence: 99%